ENDOCRINOLOGICAL ROLE OF LEPTIN IN OBESITY AND ASTHMA - K SONI, ARUN; B PITHADIA, ANAND; S DESHPANDE, SHRIKALP; N SUHAGIA, BHANUBHAI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Role of leptin resistance in correlation between obesity and asthma. Methods: High-caloric diet was given for 8 weeks to induce obesity. Ovalbumin followed by aluminum hydroxide was given to induce asthma. The animal was treated with leptin analog (0.4 mg/kg, i.p. for 7 days) and leptin antagonist (3 mg/kg, p.o., for 7 days). Biochemical parameters such as serum leptin, ghrelin, and tumor necrosis factor alpha (TNF-α) and physical parameters such as tidal volume and airflow rate were estimated to confirm the state of asthma and obesity, respectively. Results: It was found that leptin and ghrelin were elevated in obese and obese asthmatic condition, responsible for leptin resistance. Treatment with leptin analog and leptin antagonist significantly increases and decreases serum leptin levels, respectively. There was no significant change in TNF-α and ghrelin level after leptin analog treatment. The result of respiratory parameters improved with leptin analog. From our study, we found beneficial role of leptin analog in obese asthmatic condition. Conclusion: Leptin is an alternative treatment approach to treat obese asthmatic condition.